6x-2(-5x-7)=-98

Simple and best practice solution for 6x-2(-5x-7)=-98 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2(-5x-7)=-98 equation:


Simplifying
6x + -2(-5x + -7) = -98

Reorder the terms:
6x + -2(-7 + -5x) = -98
6x + (-7 * -2 + -5x * -2) = -98
6x + (14 + 10x) = -98

Reorder the terms:
14 + 6x + 10x = -98

Combine like terms: 6x + 10x = 16x
14 + 16x = -98

Solving
14 + 16x = -98

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 16x = -98 + -14

Combine like terms: 14 + -14 = 0
0 + 16x = -98 + -14
16x = -98 + -14

Combine like terms: -98 + -14 = -112
16x = -112

Divide each side by '16'.
x = -7

Simplifying
x = -7

See similar equations:

| 2s=s+23 | | 3-4(x+2)=x-10 | | c-5=20 | | 4x-6=x+3(x-5) | | 6z^3-13z^2+6z=0 | | m^3-36m=0 | | (x-5)(-5)=0 | | 3x-3+45=-3x | | -6x+6(7x-15)=198 | | 6(5x+1)=5x-8X | | 3(4x+3)=2-5(7-x) | | 164x-82=738 | | 7(3x+1)=3x-8x | | 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 | | an=5n-8 | | -9+90=9x-90 | | 5x-95=x | | -8y-2=-7y-7 | | 3-4x+6-7=42 | | lnx=0.85 | | x^2+12x=540 | | 4(x-3)+2x=10 | | 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 |

Equations solver categories